(untitled) (Medical Forum Monthly, 2024)
Objective: To assess morphological variations of superior articular facets of atlas vertebrae. Study Design: Descriptive observational study. Place and duration of study: This study was conducted at the Anatomy Department, Sheikh Zayed Medical College, Rahim Yar Khan and Wah Medical College, Wah Cantt., district Rawalpindi. Duration of this study was two years. Materials and Methods: The study included 60 dried human atlas vertebrae of unknown age and sex. The instruments were hand lens, lead pencil and markers. Morphological parameters of presence of a notch/ constriction, presence of a groove, tendency of separation, pressure facets and shape of 120 superior articular facets (SAFs) were examined and noted. Results: In superior articular facets notch/constriction on medial border was 13.33%, lateral border 15% and on both borders 40%. The SAFs without notch/constriction were 31.67%. Grooves on right, left and bilateral facets were 11.67%, 23.33% and 46.67% respectively. No groove was present in 18.33% SAF. The tendency of separation on right and left facets (right 50%, left 48.33%) showed no significant difference. Incomplete separation (right 6.66%, left 8.33%) and complete separation (right 3.33%, left 5%) was slightly more frequent on left side as compared to the right SAF. The pressure facets were present on 5% on right side, 6.66% on left side and 51.66% SAF on both sides. Regarding the shapes of SAF, dumb-bell was the most frequent (34.17%) followed by oval (31.67%) figure of eight (20.83%) and kidney shape (13.33%). Conclusion: The knowledge of quantitative anatomy of superior articular facets of atlas vertebrae will prove useful for the surgeons who perform operative procedure in this region and will help in avoiding complications.